A Case of Zoster Duplex Bilateralis - Shin, Jung Woong (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
The skin lesions of herpes zoster are classically limited to a single dermatome and most cases of multidermatomal herpes zoster have contiguous skin lesions. Simultaneous involvement of two noncontiguous dermatomes is very rare and it has been referred to as zoster duplex unilateralis or bilateralis, depending whether one or both halves of the body are involved. A 67-year-old woman presented with a group of painful vesicles on the right buttock and thigh, and left anterior chest and back. The Tzanck smear and skin biopsy were consistent with a herpetic infection. We report a rare case of zoster duplex bilateralis.